IDENTIFIKASI KESULITAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL TES URAIAN OBYEKTIF PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN (STUDI KASUS DI SMA BATIK 2 SURAKARTA) - Saputra, Galih; ., Winarno; Nuryadi, Muh Hendri (PKn Progresif, 2016)
The objectives of research was to find out: 1) how the analysis of objective essay test item organized by Pancasila and Civic Education teacher is in SMA Batik 2 Surakarta, and 2) the factors causing the student?s difficulty in solving the objective essay test item in Pancasila and Civic Education subject in SMA Batik 2 Surakarta. This study was a qualitative research approach. Data source derived from informant, place, event, and document. The sampling technique used was purposive sampling. Techniques of collecting data used were interview, observation, document analysis and Focus Group Discussion. Data validation was carried out using data and method triangulations. The results of research are as follows: 1) The analysis on objective essay test item organized by teacher included: a) in material aspect, the border of question and answer to be measured in essay test had not showed clear border yet, b) in constructing aspect, the essay test developed by teacher still had weaknesses such as no clear instruction on how to work on the intended test item, c) in language aspect, essay item developed by teacher had not used simple language, meaning that there was still too-long sentence less understandable to the students. 2) The factors causing the students? difficulty in solving the essay test included: Internal factor: a) in cognitive aspect: low cognitive ability of students, b) in affective aspect: some students still did not care with the learning, slept in the classroom, were preoccupied with themselves, and did not pay attention to teacher during the learning process, c) in psychomotor aspect: less active participation of students in discussion learning. External factor: a) Infrastructure factor: inadequate learning source availability facilitated by school for the students in the form of Student Worksheet (LKS) or other exercise book. b) Teacher factor: Pancasila and Civic Education teacher?s limited intensity in applying the assessment in the form essay question.